Protection Of Cultural Property - كريز, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Cultural property is an important place within the concerns of the international community in the modern era. All indicators suggest that conflicts and conflicts in the world affect, directly or indirectly, the elements of cultural heritage, especially cultural property. Therefore, it was necessary to lay the foundations to ensure their survival, in light of the deliberate disregard of the conflicting parties of what these features mean in determining the identity of peoples, which negatively affected these properties. So, contemplating the international scene today clearly shows the extent of the great mobility that the international community is doing in order to ensure legal protection of cultural property and keep it away from armed conflicts. Perhaps these solutions did not amount to criminalizing the parties that violate international conventions by destroying cultural monuments. Of the systematic destruction that was followed during the Second World War and its aftermath. However, these efforts are still inadequate and require deterrent sanctions that make the agreements more effective, ensuring that each party safeguards its history and cultural identity while not losing the right of future generations. This political movement was met by a legal movement with roots in international humanitarian law concerned with providing legal protection for cultural property during armed conflicts through the conclusion of many agreements that guaranteed such protection within its legal texts.